C2N: Bridging CAMARA Service APIs and 3GPP Core Network Exposure Function - Silva, Rafael Rodrigues; Esper, João Paulo; Almeida, Leandro C. de; Verdi, Fábio L.; Cardoso, Kleber V. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
The exposure of 5G network capabilities to third-party applications is fundamental for realizing the Network-as-a-Service (NaaS) paradigm. However, the complexity of native 3GPP interfaces, particularly the Network Exposure Function, creates a significant barrier for application developers. The CAMARA project addresses this challenge by standardizing developer-friendly service APIs, yet the Transformation Function that is responsible for translating these APIs into network-native interfaces remains underspecified and typically implemented as a proprietary black box. This paper presents C2N, an opensource Transformation Function for the CAMARA Traffic Influence API. We propose a modular architecture comprising seven components that implement a three-phase semantic mapping strategy: direct mapping; logical transformation with topology enrichment; and structural mapping. This approach bridges the abstraction gap between CAMARA’s developer-oriented interface and the 3GPP specification of the Network Exposure Function Northbound APIs. We validate C2N using a 5G testbed built with free5GC and UERANSIM, demonstrating successful traffic steering from a latency-degraded path to an alternative performance-satisfactory one. We make publicly available the necessary code and information for reproducibility and provide a reference for researchers investigating API translation strategies in the mobile networks NaaS ecosystem.